Does Vancomycin Resistance Increase Mortality? Clinical Outcomes and Predictive Factors for Mortality in Patients with Enterococcus faecium Infections - Jatapat Hemapanpairoa; Dhitiwat Changpradub; Sudaluck Thunyaharn; Wichai Santimaleeworagun (MDPI AG, 2021)
The prevalence of enterococcal infection, especially E. faecium, is increasing, and the issue of the impact of vancomycin resistance on clinical outcomes is controversial. This study aimed to investigate the clinical outcomes of infection caused by E. faecium and determine the risk factors associated with mortality. This retrospective study was performed at the Phramongkutklao Hospital during the period from 2014 to 2018. One hundred and forty-five patients with E. faecium infections were enrolled. The 30-day and 90-day mortality rates of patients infected with vancomycin resistant (VR)-E. faecium vs. vancomycin susceptible (VS)-E. faecium were 57.7% vs. 38.7% and 69.2% vs. 47.1%, respectively. The median length of hospitalization was significantly longer in patients with VR-E. faecium infection. In logistic regression analysis, VR-E. faecium, Sequential Organ Failure Assessment (SOFA) scores, and bone and joint infections were significant risk factors associated with both 30-day and 90-day mortality. Moreover, Cox proportional hazards model showed that VR-E. faecium infection (HR 1.91; 95%CI 1.09-3.37), SOFA scores of 6-9 points (HR 2.69; 95%CI 1.15-6.29), SOFA scores ≥ 10 points (HR 3.71; 95%CI 1.70-8.13), and bone and joint infections (HR 0.08; 95%CI 0.01-0.62) were significant risk factors for mortality. In conclusion, the present study confirmed the impact of VR-E. faecium infection on mortality and hospitalization duration. Thus, the appropriate antibiotic regimen for VR-E. faecium infection, especially for severely ill patients, is an effective strategy for improving treatment outcomes.